POPULATION, BEHAVIOUR AND CONSERVATION STATUS OF LONG-TAILED MACAQUE, Macaca fascicularis, SOUTHERN PIG-TAILED MACAQUE, Macaca nemestrina IN PAYA BAKAU PARK, PERAK, MALAYSIA - M. N. Dzulhelmi; S. Suriyanti; S. Manickam (Journal of Animal and Plant Sciences, 2019)
A study was conducted on the population and behaviour of long-tailed macaque, Macaca fascicularis and southern pig-tailed macaque, M. nemestrina in Paya Bakau Park, Perak, Malaysia. Direct field observations were taken for 20 non-consecutive days between October and December 2016. One-hour observation session was carried out on daily activity budget for both species during their ‘feeding time’ between 1700–1900 hour at the main entrance. From the field data, an average group size of 32.75±12.34 individuals of M. fascicularis and 22.60±4.84 individuals of M. nemestrina was estimated to be present during the ‘feeding time’. Resting and locomotion were the most common behaviors performed by both species. There was no significant difference in the behaviours with the exception of resting pattern between M. fascicularis and M. nemestrina (p-value: 0.007, t=2.754, df=158). Due to the ‘friendly’ and highly tolerated interaction between the individuals of both species observed during the ‘feeding time’, hybridization of the two species may occur in the future which is of high concern. Conservation measures should be taken to sustain and monitor the status of their population.
Keywords: activity budget; hybridization; intra-species; natural history; sex ratio